2006
DOI: 10.24841/fa.v12i1-2.122
|View full text |Cite
|
Sign up to set email alerts
|

BIOLOGÍA REPRODUCTIVA DE «BOQUICHICO», Prochilodus nigricans, EN LA AMAZONÍA PERUANA

Abstract: Reproduction of «boquichico» Prochilodus nigricans, at the Peruvian Amazon takesplace from December to March, coinciding with the period of water rising of theAmazon River, not showing a clear relationship with the increment of local raining.This species reaches its average size of maturity at a fork length of 24,3 cm., infemales, and 23,4 cm., in males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
1
9
0
4
Order By: Relevance
“…The hydrological regime thus appears to be a main factor influencing the reproductive cycle of this species. This pattern coincides with observations of reproduction of black prochilodus in the Peruvian Amazon (Montreuil et al, 2001), which concurred with the period of water rising in the Amazon River (December to March). Also, Stassen et al (2010) observed that changes in water chemistry following the onset of rainy season may trigger gonad development and spawning in P. lineatus (Valenciennes, 1837) in the Pilcomayo River.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The hydrological regime thus appears to be a main factor influencing the reproductive cycle of this species. This pattern coincides with observations of reproduction of black prochilodus in the Peruvian Amazon (Montreuil et al, 2001), which concurred with the period of water rising in the Amazon River (December to March). Also, Stassen et al (2010) observed that changes in water chemistry following the onset of rainy season may trigger gonad development and spawning in P. lineatus (Valenciennes, 1837) in the Pilcomayo River.…”
Section: Discussionsupporting
confidence: 64%
“…Turbulence in the larger, white water mainstreams also may help to keep the eggs and early larval stages suspended in the water column. This reproductive strategy during flood season benefits larvae and young fish that need to drift downstream where they can find a diversity of flooded environments for natural protection, as well as excellent conditions for feeding and rapid growth (Montreuil et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Welcomme (1979), Novoa & Ramos (1982), Galvis et al (1989), indican que la reproducción de muchos peces en los ríos tropicales es altamente estacional y que, en los ríos que presentan variaciones en su nivel a través del año, ocasionadas por regímenes hidrológicos variables, existe una sincronización entre los procesos reproductivos de la mayoría de peces y el incremento en el nivel de las aguas. Ciertamente con la doncella, se ha verificado que la duración de su época de reproducción, se prolonga desde noviembre hasta marzo con un pico máximo en febrero, este lapso coincide con el periodo de aguas altas del río Ucayali, comportamiento que también fue observado, para otras especies, por Guevara (1974), Basile-Martins (1978), Caramaschi (1979), Tello et al (1992) citados por Barthem et al (1995) y Montreuil et al (2001). Así mismo Lauzanne et al (1990) y Montreuil et al (2001), mencionan que las estrategias de reproducción durante las aguas altas favorece mucho a las larvas y alevinos que encuentran diversos ambientes para su protección natural en las zonas inundadas, así como también adecuadas condiciones para su alimentación y desarrollo.…”
Section: Discussionunclassified
“…El proceso reproductivo en especies ícticas de ambientes tropicales es consecuente con las características ambientales locales (Peressin, Gonçalves, & Braga, 2012), comienza generalmente en junio-julio, con una alta frecuencia de individuos maduros en septiembre-octubre (Schifino, Fialho, & Verani, 1998), ocurriendo máximos reproductivos en los meses de mayor precipitación y temperatura (Peressin et al, 2012), coincidiendo con el mayor nivel del agua (Vieira, Isaac, & Fabré, 1999;Montreuil, García, & Rodríguez, 2001).…”
unclassified